2017
DOI: 10.1016/j.bpj.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Omecamtiv Mecarbil Abolishes Length-Mediated Increase in Guinea Pig Cardiac Myofiber Ca2+ Sensitivity

Abstract: Omecamtiv mecarbil (OM) is a pharmacological agent that augments cardiac contractile function by enhancing myofilament Ca sensitivity. Given that interventions that increase myofilament Ca sensitivity have the potential to alter length-dependent activation (LDA) of cardiac myofilaments, we tested the influence of OM on this fundamental property of the heart. This is significant not only because LDA is prominent in cardiac muscle but also because it contributes to the Frank-Starling law, a mechanism by which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 50 publications
(99 reference statements)
6
32
2
Order By: Relevance
“…It can also explain the reduced OM effects at high OM levels reported by Nagy et al for both cardiac myocytes and diaphragm fibers[42], and seen here in soleus fiber bundles (S1A Fig): at high OM levels the OM-bound heads that do not generate force outnumber the additionally recruited OM-free force generating heads. The dose-response curve that we measured on cardiac muscle does not decline at high OM levels (S1B Fig) a finding similar to that of Gollapudi et al (their Fig 2)[41]. This can be explained by the short sarcomere length that was used in these studies (2.0 μm in our study and 1.9 μm in [41]), where baseline activation is low, and the long sarcomere length used by Nagy et al in their cardiac myocyte study (2.3 μm) where the baseline activation level is high.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It can also explain the reduced OM effects at high OM levels reported by Nagy et al for both cardiac myocytes and diaphragm fibers[42], and seen here in soleus fiber bundles (S1A Fig): at high OM levels the OM-bound heads that do not generate force outnumber the additionally recruited OM-free force generating heads. The dose-response curve that we measured on cardiac muscle does not decline at high OM levels (S1B Fig) a finding similar to that of Gollapudi et al (their Fig 2)[41]. This can be explained by the short sarcomere length that was used in these studies (2.0 μm in our study and 1.9 μm in [41]), where baseline activation is low, and the long sarcomere length used by Nagy et al in their cardiac myocyte study (2.3 μm) where the baseline activation level is high.…”
Section: Discussionsupporting
confidence: 90%
“…From these studies, a model was proposed in which these OM-bound heads cooperatively activate the thin filament at submaximal activation levels, recruiting OM-free myosin heads and thereby increasing force [20]. This mechanism naturally explains the sarcomere length dependence of the magnitude of the OM-effect that has been found in sub-maximally activated cardiac muscle[41], with larger OM effects at short sarcomere length where the baseline activation level of the thin filament is lower and more OM-free heads can be recruited to the force generating pool than at longer sarcomere length. It can also explain the reduced OM effects at high OM levels reported by Nagy et al for both cardiac myocytes and diaphragm fibers[42], and seen here in soleus fiber bundles (S1A Fig): at high OM levels the OM-bound heads that do not generate force outnumber the additionally recruited OM-free force generating heads.…”
Section: Discussionmentioning
confidence: 99%
“…We posit that increased XB-based cooperativity counteracts the negative impact of strained XBs on force-bearing XBs, leading to a decrease in γ at short SL. The augmenting effect of TnT F88L on XB-based cooperativity at short SL is also supported by the magnitude of ML-mediated XB recruitment, E R , which is sensitive to changes in XB-based cooperativity ( Campbell et al, 2004 ; Campbell and Chandra, 2006 ; Stelzer et al, 2006 ; Gollapudi et al, 2017 ). TnT F88L significantly increases E R at short SL (39%) but not at long SL, suggesting that TnT F88L imparts a greater effect on XB-based cooperativity at short SL.…”
Section: Discussionmentioning
confidence: 82%
“…Biochemical kinetic experiments have suggested that OM does not affect the actomyosin-detachment rate during cycling 1 , 6 , which is at odds with our findings. However, studies of tension development and relaxation rates of cardiac muscle preparations have indicated that detachment may be slowed by OM 11 , 12 , 34 . The previous biochemical conclusions 1 , 6 were based on the measurement of the rate of ADP release (the step that limits the rate of actin detachment at physiological ATP) from an AM·ADP complex formed by adding ADP to the rigor, AM complex in isolated actomyosin 1 , 6 , 9 Our results indicate that the step that limits actin detachment is not accessible by simply adding ADP, but occurs earlier in the cycle and may not be on the conventional ATPase pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%